2018
DOI: 10.1002/ejoc.201800224
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation of Allenes Over Palladium–Gold Alloy Catalysts: Enhancing Activity and Switching Selectivity by the Incorporation of Palladium into Gold Nanoparticles

Abstract: An efficient synthetic route to alkenylsilanes involving the hydrosilylation of allenes with supported Pd–Au alloy catalysts has been developed. The incorporation of Pd atoms into Au nanoparticles remarkably enhanced the catalytic activity and product selectivity. Pd–Au alloy catalysts with a low Pd/Au ratio were highly effective for the hydrosilylation at an ambient temperature, and the corresponding β‐alkenylsilanes were obtained as a main product in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Moreover, our group reported in 2015 the stereoselective hydrosilylation of internal alkynes by recyclable rhodium nanoflowers stabilized by a nitrogen‐rich PEG‐tagged substrate . Finally, some metal based nanocrystals (Pt, Ir, Rh, Ru) stabilized by Onium salts were studied as catalysts in the addition of silanes to terminal alkynes and palladium‐gold alloys for the hydrosilylation of allenes …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our group reported in 2015 the stereoselective hydrosilylation of internal alkynes by recyclable rhodium nanoflowers stabilized by a nitrogen‐rich PEG‐tagged substrate . Finally, some metal based nanocrystals (Pt, Ir, Rh, Ru) stabilized by Onium salts were studied as catalysts in the addition of silanes to terminal alkynes and palladium‐gold alloys for the hydrosilylation of allenes …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, AuPd nanoalloys have been shown to catalyze different transformations . For example, Shishido and co‐workers described the hydrosilylation of alkynes or α,β‐unsaturated ketones to provide vinylsilanes or silyl enol ethers and also showed that the hydrosilylation of allenes to internal alkenylsilanes can be achieved with such nanoparticles . Recently, we studied the cooperative activity of AuPd nanoalloys in selective hydrogenation of internal alkynes to the corresponding Z‐alkenes .…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the catalysis based on the alloy catalysts has gained much attention in the field of synthetic chemistry. In the case of bimetallic catalysts, the palladium–gold (Pd–Au) alloy catalyst is of interest because of the wide variety of catalytic activity, particularly due to the monometallic Pd site. , For example, the Pd–Au alloy nanoparticle shows considerable catalytic activity in the oxidation of alcohols, polyols, , and hydrocarbons. , The catalytic activity of the Pd–Au alloy nanoparticle was also identified in organic synthesis. In 2012, the colloidal-phase Pd–Au bimetallic nanoparticle was observed to catalyze Ullmann coupling of aryl chlorides under mild reaction conditions while the monometallic Au or Pd nanoparticle did not show any activity. Later, Yamamoto and Jin et al reported the 1,4-hydrosilylation of cyclic α,β-unsaturated ketones applying the nanoporous Pd–Au alloy catalyst at elevated temperature . More recently, Miura and Shishido et al have developed highly active supported Pd–Au alloy catalyst for the hydrosilylation of α,β-unsaturated ketones as well as internal alkynes. , They found the catalytic performance was significantly influenced by the atomic ratio of Pd/Au and the supporting material. More importantly, the low Pd/Au atomic ratio with isolated single Pd atom surrounded by the Au atoms is important for the highly efficient and selective hydrosilylation of various unsaturated compounds under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…46 More recently, Miura and Shishido et al have developed highly active supported Pd−Au alloy catalyst for the hydrosilylation of α,β-unsaturated ketones as well as internal alkynes. 47,48 They found the catalytic performance was significantly influenced by the atomic ratio of Pd/Au and the supporting material. More importantly, the low Pd/Au atomic ratio with isolated single Pd atom surrounded by the Au atoms is important for the highly efficient and selective hydrosilylation of various unsaturated compounds under mild reaction conditions.…”
Section: ■ Introductionmentioning
confidence: 99%